Pengelolaan Anggaran Desa di Desa Warawatung, Kecamatan Nagawutun, Kabupaten Lembata - Yohana Wilantari Mali; Tekla Harcici Yevin; Adriana Florinda Ganus; Bergitha Fuamuni; Yosep Riang; Frans Nyong (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
Village budget management is the process of planning, allocating, using and supervising funds owned by a village. Good village budget management aims to improve the welfare of village communities through targeted and efficient development. The method of implementing work programs is through socialization and interviews by program implementers. work and work program targets. Good Village Budget Management can bring Warawatung Village to a prosperous, developing and advanced village,